Peran Penyuluh Agama dalam Memotivasi Kepala Keluarga untuk Mencari Nafkah di Kabupaten Majalengka - Asmawiyah, Wiwin (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2022)
Abtsract: Islamic Religious Counslors has a quite strategic role in the midst of society. Besides he is a preacher of Islam, also the Islamic Religious Counselors, according to his function as a guide, illuminator, and community builder with religious language. The role of religious counselors in addition to functioning as an impetus for the community to actively participate in development also plays a role in overcoming obstacles that build the course of development, particularly overcoming negative impacts. Religious counselors as religious leaders always guide, nurture, and move the community to do good and stay away from prohibited acts, inviting something that is needed by the community in fostering its territory both for the purposes of social facilities and worship. The Religious Counselors is a place to ask questions and a place to complain for his community to solve and resolve the problem with his advice. Religious Counselors as community leaders act as priests in matters of religion and social problems as well as in matters of state by an effort to succeed the government program. This study is aimed to know The role of Religious Counselors in motivating head of family to earn a living in Majalengka City, it can be concluded that religious counselors play an important role in motivating head of family to earn a living. One of which is with terms to give understanding to them, that to earn the living not only as an obligation a head of family, but also set an example for his next generation, especially his son. To be responsible head of family at a later time.Abtsrak: Penyuluh Agama Islam memiliki peranan yang cukup strategis di tengah-tengah masyarakat. Selain sebagai pendakwah Islam, Penyuluh Agama Islam juga, sesuai dengan fungsinya sebagai pembimbing, penerang, dan pembangun masyarakat dengan bahasa agama. Peranan penyuluh agama selain berfungsi sebagai pendorong masyarakat untuk berpartisipasi aktif dalam pembangunan, berperan juga ikut serta mengatasi hambatan yang membangun jalannya pembangunan, khususnya mengatasi dampak negatif. Penyuluh agama sebagai pemuka agama selalu membimbing, mengayomi, dan menggerakkan masyarakat untuk berbuat baik dan menjauhi perbuatan yang terlarang, mengajak kepada sesuatu yang menjadi keperluan masyarakatnya dalam membina wilayahnya baik untuk keperluan sarana kemasyarakatan maupun peribadatan. Penyuluh Agama menjadi tempat bertanya dan tempat mengadu bagi masyarakatnya untuk memecahkan dan menyelesaikan masalah dengan nasehatnya. Penyuluh Agama sebagai pemimpin masyarakat bertindak sebagai imam dalam masalah agama dan masalah kemasyarakatan begitu pula dalam masalah kenegaraan dengan usaha menyukseskan program pemerintah. Salah satunya dengan membantu mewujudkan kesejahteraan rakyat. Tujuan penelitian ini adalah untuk mengetahui sejauh mana peran Penyuluh Agama memotivasi kepala keluarga yang ada di Kabupaten Majalengka Provinsi Jawa Barat untuk mencari nafkah. Kegiatan tersebut di lakukan dengan memberikan pemahaman dan pendampingan kepada mereka bahwa mencari nafkah tidak hanya sebagai kewajiban kepala keluarga, tetapi juga memberikan teladan bagi generasi penerusnya yaitu anak-anaknya terutama anak laki-lakinya. Agar menjadi kepala keluarga yang bertanggungjawab di masa yang akan datang.